Care and nutrition: concepts and measurement - Engle, Patrice L.; Menon, Purnima; Haddad, Lawrence J. (International Food Policy Research Institute, 1996)
Care is the provision in the household and the community of time, attention and support to meet the physical, mental, and social needs of the growing child and other household members (ICN 1992). This provision of time, attention, and support is manifest in certain types of behaviors exhibited by caregivers (typically women) : (1) care for pregnant and lactating women, such as providing appropriate rest time or increased food intake; (2) breast-feeding and feeding of very young children; (3) psychosocial stimulation of children and support for their development; (4) food preparation and food storage behaviors; (5) hygiene behaviors; and (6) care for children during illness, including diagnosis of illness and health-seeking behaviors (Engle 1992). Provision of these behaviors depends on the availability of the resources for care at the household level: education and knowledge, health of the caregiver, time, autonomy, and social support. Although many researchers over the past 30 years have emphasized the importance of behavioral factors for adequate child growth in conditions of poverty and food constraints (Sims, Paolucci, and Morris 1972), the linkages between food availability, caregiving behaviors, and child nutrition are now being recognized at a policy level (ICN 1992). The conceptual model underlying the role of care in child nutrition has been applied more frequently over the past 10 years (UNICEF 1990). This paper will review new conceptual developments and the implications for the measurement and monitoring of care resources and care behaviors. Section 2 reviews the evolution of the original care conceptual model. Sections 3 and 4 review the development of indicators for care resources and care behaviors, respectively. Section 5 concludes with suggestions for further research.